Minat Pemilik Usaha Industri Kerajinan Bambu Dalam Program Kredit Usaha Rakyat (KUR) Di Kabupaten Bangli - Kartika Dewi, Ni Luh Putu; Purbadharmaja, Ida Bagus Putu (Jurnal Ekonomi Kuantitatif Terapan, 2019)
The development of bamboo handicraft business can’t be separated from the important role of capital, KUR is a working capital or investment financing specifically intended for SMEs in the field of productive and feasible business. This study aims to analyze the interest of bamboo handicraft industry business owners in KUR program, and analyze the partial and simultaneous effect of program socialization, knowledge, interest rate perception and revenue on the interest of bamboo handicraft industry owners in KUR program in Bangli regency. In this study dependent variable is dummy and primary data type. Data analysis technique used is logit model. The result of analysis shows that bamboo handicraft business owners who are interested in KUR program are 74.74 percent. Program socialization, knowledge, interest rate perception and revenue have a positive and significant effect to interest of bamboo handicraft business owners in KUR program either partially or simultaneously.